Urban traffic system, 2nd ed. - Kadar Hamsa, Abdul Azeez (IIUM Press, International Islamic University Malaysia, 2020)
Urban Traffic System constitutes a group of interdependent and interrelated traffic and related components which are intended to form a unified entity to accomplish smooth, orderly and safe movement of vehicles in an urban area. The number of trips being attracted to urban areas is normally very high due to the presence of high density commercial and business land uses. In the local context, these trips to the urban areas were usually performed by private vehicles and thus has increased the number of private vehicles entering into the urban areas on a daily basis. Due to limited road and other transport infrastructure in urban areas, the increasing number of private vehicles has caused continuing increase in the level of traffic congestion, thereby decreasing the speed of the vehicles, increasing the travel and delay time, increasing the air pollution level and increasing the discomfort and inconveniences of the road users. It is very import to understand the effects of the increase in traffic on road and other transport infrastructure. The first edition of this book covers topics on traffic volume, speed, road intersection, road capacity, level of service, parking, traffic control devices, road safety, and traffic management measures including traffic calming.